2016
DOI: 10.1016/j.bpj.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of Venous Thrombosis Initiation

Abstract: We present a mathematical model for the initiation of venous thrombosis (VT) due to slow flow and the consequent activation of the endothelial cells (ECs) lining the vein, in the absence of overt mechanical disruption of the EC layer. It includes all reactions of the tissue factor (TF) pathway of coagulation through fibrin formation, incorporates the accumulation of blood cells on activated ECs, accounts for the flow-mediated delivery and removal of coagulation proteins and blood cells from the locus of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…Using the D-dimer assay, the first measurement of intrathrombus fibrin concentration revealed that fresh fibrinogen substrate can also continually enter the clot and be converted to fibrin monomer and incorporated into fibrin. While the binding of thrombin into fibrin has been studied in the literature, 30 the conditions of a thrombus formed under flow are unique relative to those found in a tube of clotting blood or plasma. Clearly, γ′-fibrin can bind endogeneously produced thrombin to a significant extent (Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the D-dimer assay, the first measurement of intrathrombus fibrin concentration revealed that fresh fibrinogen substrate can also continually enter the clot and be converted to fibrin monomer and incorporated into fibrin. While the binding of thrombin into fibrin has been studied in the literature, 30 the conditions of a thrombus formed under flow are unique relative to those found in a tube of clotting blood or plasma. Clearly, γ′-fibrin can bind endogeneously produced thrombin to a significant extent (Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first model to track limited numbers of cell binding sites [ 12 ] is the original version of the model considered in this paper. That model was further developed in [ 14 , 16 , 20 , 21 ] and inspired similar models [ 4 , 6 ]. These models account for reversible binding of proteins to these sites with rates k on and rates k off for binding and unbinding, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although these concentrations are below the threshold values of 500 and 800 pM that are required to activate platelets and factors V and XIII, 3 one can expect that these plasma levels induce a hypercoagulable state when reaching low flow areas or areas of circulating flow such as in the valve pockets. 14,15 To estimate the relation between the total amount of thrombin formed and the amount of thrombin that is released into the circulating blood, plasma levels of F1.2 were compared with plasma levels of thrombin and TAT. Plasma levels of F1.2 significantly increased during surgery, whereas plasma levels of TAT were measured within the same molar ranges as F1.2.…”
Section: Discussionmentioning
confidence: 99%